Impact of Chemicals on the Age of Menarche: A Literature Review - Xristos Anastasiadis; Alkis Matsas; Theodoros Panoskaltsis; Panagiotis Bakas; Dimitrios T. Papadimitriou; Panagiotis Christopoulos (Children, 2023)
A growing body of evidence suggests that chemicals interfere with the age of onset of menarche. We conducted a review in order to demonstrate the relationship between several categories of chemicals and menarche. We searched for English language papers using the Medline/PubMed database until April 2023. The chemical factors found to affect menarche were prenatal and antenatal smoke, phthalates, phenols, organochlorines, perfluoroalkyls and polyfluoroalkyls, metals, air pollutants and polybrominated diphenyl ethers. Low or high exposure to each chemical compound could affect the age of menarche, leading to early or delayed menarche. Furthermore, the results show that intrauterine exposure may have a different impact from antenatal exposure. There is evidence that endocrine-disrupting chemicals affect the age of menarche, but more research needs to be conducted.